KEDUDUKAN HUKUM SURAT PERNYATAAN PENOLAKAN WARIS YANG DIBUAT OLEH NOTARIS BERDASARKAN PASAL 1057 KITAB UNDANG-UNDANG HUKUM PERDATA DAN PASAL 15 (1) UU NOMOR II TAHUN 2014 TENTANG JABATAN NOTARIS - Ana Maria Clarisa Dhiu Sawi; Tahegga Primananda Alfath; Sri Wahyu Jatmikowati (Law Jurnal, 2026)
This research examines the legal standing of a declaration of inheritance refusal deed made by a notary based on Article 1057 of the Indonesian Civil Code. The issue studied is whether a notarial deed can serve as a valid legal instrument for inheritance refusal, and what legal consequences arise from such a deed under civil inheritance law. This study uses a normative legal research method with statutory, conceptual, and case approaches. The legal materials analyzed consist of primary, secondary, and tertiary legal sources, which are interpreted descriptively and qualitatively. The findings show that inheritance refusal under Article 1057 of the Civil Code must be expressed clearly through a statement submitted to the district court registry, as required by law. Therefore, a notarial deed of inheritance refusal functions primarily as written evidence of the heir’s intention, but it does not automatically replace the formal procedure required by law. Accordingly, a notarial deed of inheritance refusal has evidentiary value as an authentic deed regarding the existence of the statement, yet it does not by itself produce legal consequences of inheritance refusal unless the statutory procedure is fulfilled. In this context, the notary must ensure that the contents of the deed reflect the parties’ intentions and do not conflict with applicable laws and regulations.